Bread and peace (C.W. Daniel Company, 1949)
Collectie Oorlog en Vrede. A paper prepared for the Pacifist Research Bureau Conference on 31st January 1948, completely revised for presentation to the International Conference of the War Resisters' International at Shrewsbury, August 1948.